Corrosion mitigation on orthodontic wire made of SS 18/8 alloy using esomeprazole tablet (Esiloc-40 mg) in artificial saliva - Akbar A.S. Begum; Raja M.A. Vahith; Mohamed K.V. Mohamed; Vijay Kotra; Baji Shaik; Abdullah Al-Kahtani (Journal of Saudi Chemical Society, 2023)
The corrosion inhibition of orthodontic wire made of SS 18/8 alloy in artificial saliva, with and without the presence of tablet esomeprazole − 40 mg has been investigated by electrochemical analysis. Polarisation study indicates that in the presence of the mentioned tablet, polarisation resistance (Rp) value increases and corrosion current (Icorr) decreases. That is, the corrosion resistance of SS 18/8 alloy in artificial saliva increases. AC impedance spectroscopy reveals that charge transfer resistance value (Rct) value increases and double layer capacitance value (Cdl) decreases. The open circuit potential (OCP) values for the inhibited system are more negative than that of the uninhibited blank system. The vibration peaks obtained from the FTIR spectra indicates the presence of functional group in esomeprazole pill and these characteristic peaks are slightly shifted in the analyzed scratched film from the surface of the orthodontic wire after immersion. AFM micrograph image of the polished specimen sample immersed in artificial saliva (AS) with esomeprazole tablet solution shows lesser degree of surface deterioration than those for SS 18/8 specimen immersed only in artificial saliva. From the present work, it is reported that people clipped with orthodontic wire made of SS 18/8 alloy need not worry about orthodontic corrosion for taking esomeprazole tablet for the treatment of gastro esophageal reflux disease and other medicinal purpose.